Pengaruh Senam Bugar Lanjut Usia Terhadap Tekanan Darah Dan Kualitas Hidup Pada Lanjut Usia Hipertensi - Nooryana, Syavira; , Isnaini Herawati, S.Fis.,Ftr.,M.Sc; , Yulisna Mutia Sari, SSt.FT., M.Sc (GRS) (2015)
Background: The number of elderly in Indonesia is increasing. An increase in the number of elderly need attention because the elderly are at high risk of various health problems, especially degenerative diseases. The main health problems that often occur in the elderly one of which is high blood pressure (hypertension). Hypertension can lead to decreased quality of life of the elderly. Hypertension treatment can be done by improving lifestyle (non-pharmacological therapy) and pharmacological therapy. One way that can be done to improve the lifestyle is by doing regular physical exercise and physical exercise that is suitable for the elderly, namely gymnastics elderly. Objective: To determine the effect of gymnastics elderly on blood pressure and the quality of life in elderly hypertension. Benefits Research: To add knowledge about the influence of gymnastics elderly on blood pressure and the quality of life in elderly hypertension. Methods: This study use quasi-experimental research methods study with one group pretest-posttest design. Total sample of 12 respondents. Selection of the sample of elderly people aged 60-74 years (elderly) with a history of hypertension ≥ 1 year and respondents had systolic blood pressure ≥ 140 mmHg and diastolic ≥ 90 mmHg. Collecting data using questionnaire The World Health Organization Quality of Life (WHOQOL)-BREF to determine the personal data as well as quality of life of the elderly and shpygmomanometer needle to measure his blood pressure. Statistical analysis using Wilcoxon Signed Ranks Test. Results: Based on a statistical analysis of the effect obtained gymnastics elderly on blood pressure significantly (ρ = 0.002 < 0.05) and the influence of gymnastics elderly on quality of life (ρ = 0.031 (physical domain), ρ = 0.005 (psychological domain), ρ = 00.11 (social domain), ρ = 0.017 (domain environment) < 0,05) Conclusion: Gymnastics elderly significantly influence the decrease in blood pressure and an increase in the value of the quality of life in elderly patients with hypertension in IHC Elderly Welfare, Kartasura.